WEBSITE RESEARCH AS A SOURCE OF ONLINE INFORMATION FOR STUDENTS IN STUDYING ISLAM - Isan; Nurul Anida; Mir'atun Nur Arifah (Universitas Islam Indonesia, 2023)
The development of information technology takes place rapidly along with the development of an increasingly advanced era. This also has an impact on the ease of access to information anywhere and anytime. The information accessed is not only related to general information, but also information related to religious knowledge. However, not all websites/sites that seek information can be trusted, so accuracy and caution are needed in processing the information obtained. This study aims to find out websites that are used as references for students in studying Islam and students' considerations in believing in the information obtained on these websites.This study uses a descriptive qualitative research method involving students of the Universitas Islam Indonesia from various majors and years. Determination of informants is done through purposive sampling technique and data collected through interviews. Analysis of the data that has been collected is carried out through data reduction, data presentation, and drawing conclusions. The results of this study show that in general there are 7 websites that are used as references for students in studying Islam, including guidanceislam.com, islam.nu.or.id, yotube.com, muslim.or.id, studisyariah.com, rumaysho, suara Muhammadiyah. The reason students trust the information obtained from the website is because the ustadz have an understanding of ahlussunah wal jama'ah and are trusted, the information provided is complemented by aqli arguments, naqli arguments, as well as scientific sanad, relevant to the book being read, and the website used is trusted.